PENCEGAHAN PEREDARAN GELAP NARKOTIKA DI WILAYAH HUKUM SUMATERA UTARA - Deddy Z Harahap; Alpi Sahari; Ahmad Fauzi (Journal Recht (JR), 2022)
Based on the data obtained that the majority of correctional facilities in prisons are 70% of the perpetrators ofcriminal acts of narcotics abuse who believe that the perpetrators of crime (vijtim) namely victims and drugaddicts, this illustrates that the level of narcotics abuse has increased from year to year. The interesting thingin narcotics crime is legal protection for victims of narcotics abuse, because there must be victims of crime. Thepurpose of this study was to analyze the role of the North Sumatra Regional Police Directorate of Drugs inpreventing narcotics illicit trafficking and the obstacles of the North Sumatra Regional Police NarcoticsDirectorate in preventing illicit trafficking of narcotics. The results of this study indicate that the obstaclesexperienced by the drug directorate are internal and external barriers which include the non-optimalmechanism for the implementation of the prevention of illicit drug trafficking both demand reduction, supplycontrol, and harm reduction, therefore systematic and conceptual steps need to be taken throughimplementation of directing, devolving, coordinating, and controlling. Efforts made by the North SumatraRegional Police Directorate still need to be developed both at the primary prevention, secondary preventionand secondary prevention and tertiary prevention stages. structuring information technology, empoweringNGOs and community components, as well as making efforts to prevent the illicit circulation of narcotics.